Correlation Between Lung Density Changes Under Different Dose Gradients and Radiation Pneumonitis—Based on an Analysis of Computed Tomography Scans During Esophageal Cancer Radiotherapy - Du, Feng; Liu, Hong; Wang, Wei; Zhang, Yingjie; Li, Jianbin (Frontiers in Oncology, 2021)
Purpose To assess the relationship between different doses of radiation and lung density changes and to determine the ability of this correlation to identify esophageal cancer (EC) patients who develop radiation pneumonitis (RP) and the occurrence time of RP. Methods A planning computed tomography (CT) scan and a re-planning CT scan were retrospectively collected under institutional review board approval for each of 103 thoracic segment EC patients who underwent radiotherapy (RT). The isodose curve was established on the planning CT with an interval of 5Gy, which was used as the standard for dividing different gradient doses. Planning CT and re-planning CT scans were matched and the mean lung CT value (HU) between different doses gradients was automatically obtained by the software system. The density change value（ΔHU）was the difference of CT value between each dose gradient before and after treatment. The correlation between ΔHU and the corresponding dose was calculated as well as the regression coefficients. Additionally the correlation between ΔHU and the occurrence and time of RP (< 4weeks, 4～12 weeks, > 12weeks) was calculated. Results The radiation dose and ΔHU was positively correlated, but the correlation coefficient and regression coefficient were lower, 0.261 (P <0.001) and 0.127 (P <0.001), respectively. With the increase of radiation dose gradient，ΔHU in RP≥2 group was higher than that in RP＜2 group, and there was significant difference between two groups in ΔHU20-25, ΔHU25-30, ΔHU30-35, ΔHU35-40, ΔHU40-45, ΔHU45-50 (p<0.05). The occurrence time of RP was negatively correlated with the degree of ΔHU (P<0.05), with a high correlation coefficient (Y=Week actual value -0.521, P<0.001) (Y=Week grade value -0.381, P=0.004) and regression coefficient (Y=Week actual value -0.503, P<0.001) (Y=Week rating value -0.401, P=0.002). Conclusions A relationship between radiation dose and lung density changes was observed. For most dose intervals there was an increase of ΔHU with an increased radiation dose, although low correlation coefficient. ΔHU were obvious after irradiation with dose ≥20Gy which was closely related to the occurrence of RP. For patients with RP, the more obvious ΔHU, the earlier the occurrence of RP, there was a significant negative correlation between them.